Literature Review of The Development of a Green Campus Teaching Factory-Based Learning Model in Vocational Schools in Indonesia - Saputro, Ida Nugroho (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research is a literature review of the development of teaching and learning models in factories developed to create an education system capable of producing industry standard products or services. The literature review method is used in this article with references adapted to the research results. The discussion presented includes an analysis of vocational education about the basic philosophy of vocational education and the characteristics of vocational education, as well as models of administering vocational education. Furthermore, the development of the teaching factory learning model which includes Project-Based Learning (PBL) and Work-Based Learning (WBL) understands the context of its development. A study of the green campus-based teaching factory approach is then reported to determine the factors that influence it. In the final section, potential research and development related to the development of a teaching factory is presented to outline potential studies.